Molecular Structure, Spectral Investigations, Hydrogen Bonding Interactions and Reactivity-Property Relationship of Caffeine-Citric Acid Cocrystal by Experimental and DFT Approach - Verma, Priya; Srivastava, Anubha; Srivastava, Karnica; Tandon, Poonam; Shimpi, Manishkumar R. (Frontiers in Chemistry, 2021)
The pharmaceutical cocrystal of caffeine-citric acid (CAF-CA, Form II) has been studied to explore the presence of hydrogen bonding interactions and structure-reactivity-property relationship between the two constituents CAF and CA. The cocrystal was prepared by slurry crystallization. Powder X-ray diffraction (PXRD) analysis was done to characterize CAF-CA cocrystal. Also, differential scanning calorimetry (DSC) confirmed the existence of CAF-CA cocrystal. The vibrational spectroscopic (FT-IR and FT-Raman) signatures and quantum chemical approach have been used as a strategy to get insights into structural and spectral features of CAF-CA cocrystal. There was a good correlation amongst the experimental and theoretical results of dimer of cocrystal, as this model is capable of covering all nearest possible interactions present in the crystal structure of cocrystal. The spectroscopic results confirmed that (O33-H34) mode forms an intramolecular (C25=O28∙∙∙H34-O33), while (O26-H27), (O39-H40) and (O43-H44) groups form intermolecular hydrogen bonding (O26-H27∙∙∙N24-C22, O39-H40∙∙∙O52=C51 and O43-H44∙∙∙O86=C83) in cocrystal due to red shifting and increment in bond length. The quantum theory of atoms in molecules (QTAIM) analysis revealed (O88-H89∙∙∙O41) as strongest intermolecular hydrogen bonding interaction with interaction energy −12.4247 kcal mol−1 in CAF-CA cocrystal. The natural bond orbital (NBO) analysis of the second-order theory of the Fock matrix highlighted the presence of strong interactions (N∙∙∙H and O∙∙∙H) in cocrystal. The HOMO-LUMO energy gap value shows that the CAF-CA cocrystal is more reactive, less stable and softer than CAF (API). The electrophilic and nucleophilic reactivities of atomic sites involved in intermolecular hydrogen bond interactions in cocrystal have been demonstrated by mapping electron density (ED) isosurfaces over electrostatic potential (ESP) i.e. plotting molecular electrostatic potential (MESP) map. The molar refractivity value of cocrystal lies within the set range by Lipinski and hence it may be used as orally active form. The results show that the physicochemical properties of CAF-CA cocrystal are enhanced in comparison to CAF (API).